If we substitute equation (2) into (1) then we have the equivalent equations; y = 5 - x and 5 - x = 9x².
An equation must contain two sets of variables, the independent variable and the dependent variable separated by the equality sign.
In this case, the original system of equations are; y = 9x² and x + y = 5. It the follows that, if we substitute equation (2) into (1) then we have the equivalent equations; y = 5 - x and 5 - x = 9x².
Learn more about mathematical equations:https://brainly.com/question/19939553
#SPJ4